ANALISIS KESESUAIAN MODEL INFILTRASI HORTON DAN PHILIPS PADA BERBAGAI PENGGUNAAN LAHAN DI SUB DAS PROGO HULU - Ritawati, Sri (Jurnal Agroekoteknologi, 2011)
The objective of this research were analyzed the suitability of Horton and Philips infiltration models in various land use in upper Progo sub watersheds. Infiltration rate was measured in the field used inundation method by double ring infiltrometer. This research also needed soil physic data, shape and land use area of upper Progo sub watersheds. Models were tested by comparing measurement infiltration rate and infiltration rate of the model, were tested statistically using correlation coefficient (R), deterministic coefficient (R2), and paired test (T test). The test results showed that Tcounted value were smaller than Ttable for both Horton and Philips infiltration model at various types of land use, but R and R2 value of Philips infiltration model higher than Horton. Conclusion of this research, that both Philips and Horton infiltration models were still quite suitable for determination infiltration rate in upper Progo sub watersheds. Philips infiltration model was better because simpler, constants more easily searchable, and not too influenced by subjectivity.Keywords : infiltration models, land use, suitability analysis, watersheds